Metagenomic Analysis of Antibiotic-Induced Changes in Gut Microbiota in a Pregnant Rat Model - Khan, Imran; Azhar, Esam I.; Abbas, Aymn T.; Kumosani, Taha; Barbour, Elie K.; Raoult, Didier; Yasir, Muhammad (Frontiers in Pharmacology, 2016)
Food and Drug Administration (FDA, USA)-approved category B antibiotics are commonly prescribed to treat infections during pregnancy. The aim of this study was to investigate antibiotic-induced changes in gut microbiota (GM) that occur during pregnancy. The 16S rRNA amplicon deep-sequencing method was used to analyse the effect of category B antibiotics (azithromycin, amoxicillin and cefaclor) on GM during pregnancy using a rat model. The GM composition was substantially modulated by pregnancy and antibiotics administration. Firmicutes, Bacteroidetes, Proteobacteria, Chlamydiae, Actinobacteria and Cyanobacteria were the dominant phyla. Antibiotic treatment during pregnancy increased the relative abundance of Proteobacteria and reduced Firmicutes. The genera Shigella, Streptococcus, Candidatus Arthromitus and Helicobacter were significantly (p<0.05) more abundant during pregnancy. Antibiotics significantly (p<0.05) reduced the relative abundance of Lactobacillus but increased that of Enterobacter. There was a significant (p<0.05) decrease in Lactobacillus sp., Lactobacillus gallinarum and Lactobacillus crispatus during pregnancy. Antibiotic treatment reduced bacterial diversity; the lowest number of operational taxonomic units (OTUs) were detected in the cefaclor-treated groups. Antibiotics significantly (p<0.05) promoted weight gain during pregnancy, and increased relative abundance of Shigella sonnei, Enterococcus hormaechei and Acinetobacter sp. GM perturbations were accompanied by increases in Proteobacteria abundance and weight gain in pregnancy following antibiotic treatment